Cloud Computing System Based on Trusted Computing Platform - Zhidong Shen; Li Li; Fei Yan; Xiaoping Wu (2010 International Conference on Intelligent Computation Technology and Automation, 2010)
Cloud computing provides people a way to share large mount of distributed resources belonging to different organizations. That is a good way to share many kinds of distributed resources, but it also makes security problems more complicate and more important for users than before. In this paper, we analyze some security requirements in cloud computing environment. Since the security problems both in software and hardware, we provided a method to build a trusted computing environment for cloud computing by integrating the trusted computing platform (TCP) into cloud computing system. We propose a new prototype system, in which cloud computing system is combined with Trusted Platform Support Service (TSS) and TSS is based on Trusted Platform Module (TPM). In this design, better effect can be obtained in authentication, role based access and data protection in cloud computing environment.